Aristotle and the Privation Theory of Evil - Ali Nikzad; Ghasem Pourhasan (حکمت و فلسفه, 2024)
According to the privation theory of evil, evil is the privation of something that a thing should naturally possess on account of its species. This definition of privation is introduced by Aristotle, but Aristotle himself has never explicitly equated evil with privation. In Categories, Aristotle has clearly stated that evil is the contrary of good. This is despite the fact that according to the privation theory of evil, good and evil are an instance of possession and privation, with evil being the privation of good. However, certain passages in Aristotle's Metaphysics appear to support the privation theory of evil. This article will examine the evidence both for and against the privation theory of evil in Aristotle's works. It will argue that (1) the evidence from Metaphysics regarding the privation theory of evil should be considered in the light of the intricate relationship between the opposition of contrariety and the opposition of possession and privation in Aristotle's philosophy, and (2) the evidence supporting the existential approach to evil in Aristotle extends beyond just Categories.